Culture and Society in the Taliban’s Deobandi Theological School - Sorkhi, Saeed; Abedi Renani, Ali; Karbalaei Pazooki, Ali (Revista de Cultura Teológica, 2025)
The emergence of the Taliban traces back to the Afghan Civil War in the 1990s, following the withdrawal of Soviet forces from Afghanistan. Amid the power vacuum, the Taliban, with its roots in religious seminaries (madrasas) in Pakistan, rapidly gained ground, enforcing a strict interpretation of Sharia law across territories under their control. The year 2021 witnessed a swift and dramatic resurgence of the Taliban, culminating in their capture of Kabul and subsequent assumption of control over Afghanistan. Despite years of international intervention and efforts to build Afghan security forces, the Taliban capitalized on widespread discontent, military vulnerabilities, and the withdrawal of foreign troops to rapidly seize territory across the country. The Taliban’s resurgence is deeply intertwined with societal factors, including grievances against corruption, inefficiency, and insecurity under the previous Afghan governments. Additionally, their promise of restoring law and order resonated with segments of Afghan society disillusioned by years of conflict and instability. The resurgence of the Taliban in Afghanistan and the significance of understanding their ideological beliefs have become pivotal amid the recent events unfolding in the country. Rooted in complex historical, social, and political factors, the return to power of the Taliban reflects a multifaceted narrative that necessitates a deeper examination of their ideological underpinnings. the main question of the present research is “What impact did social theology have on the conditions and situation of society under the rule of the Taliban in Afghanistan?”